Overlapping-generations economies under uncertainty: Dynamic inefficiency/efficiency with multiple assets and no labour - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2023)
The paper gives conditions for effi ciency and ineffi ciency of equilibrium allocations in an overlapping-generations model with a constant rate of population growth and with multiple assets, but without labour. Optimal portfolio choice implies that, for any period and history up to that period, the conditional certainty equivalents of the one-period-ahead marginal rates of return must be the same for all assets that are held in positive amounts. The effi ciency or ineffi ciency of equilibrium allocations depends on whether this common conditional certainty equivalent of returns on assets is larger or smaller than the population growth rate. If the growth rate is uncertain, the standard of comparison is the certainty equivalent of the population growth rate when interpreted as a marginal rate of return on an asset.
hdl:21.11116/0000-000D-1B91-1
Keywords: D15; D61; E21; E22; E62; H30; 330; Dynamic Inefficiency; overlapping-generations models; First Welfare Theorem; certainty-equivalents criterion